The virtuosos of policing - Tafoya, William L. (American journal of criminal justice, 1990)
This paper reports the findings of a nationwide survey undertaken in order to address the issue of who the experts are in the field of law enforcement management. The results reflect the opinion of the leadership of the nation’s most prominent practitioner and academic professional criminal justice and law enforcement organizations. Thirty-seven individuals emerge as the leading law enforcement management experts-the virtuosos. Of these, eight are characterized as the nation’s elite.